The Impact of Work Environment and Transactional Leadership Style on Employees’ Performance - AYSE GUL UZUNDEMIR; ALBATTAT, AHMAD; FORBIS AHAMED (International Journal of Multidisciplinary Research and Studies, 2023)
Tourism has aided Malaysia's rapid economic growth; it is the third greatest contributor to Malaysia's GDP, after manufacturing and commodities. The hotel business also contributes to the growth of domestic and international tourism. Given the quick annual changes in the tourism industry and the unexpected shift in the economic environment, hotel owners should rethink their client loyalty and performance plans. Furthermore, the international environment, such as the global spread of contagious diseases, might have an impact on hotel performance. The travel and tourism business has been hit hard by the COVID-19 outbreak. Using a literature review, this research discovered that organizations in the hospitality industry rely heavily on their employees as service providers to gain a competitive advantage and long-term success. As seen in the service profit chain, contented staff can improve tourist satisfaction and raise hotel profitability. Furthermore, satisfied employees are thought to diminish disengagement intents and foster organizational citizenship. This study intends to evaluate employee job satisfaction and its link with attrition intentions and organizational citizenship behaviors in the context of Malaysian hospitality.